Analisis Beban Kerja Terhadap Keinginan Keluar Kerja Karyawan Melalui Stres Kerja Sebagai Variabel Intervening - Darmastuti, Ismi (JURNAL STUDI MANAJEMEN ORGANISASI, 2024)
This study aims to understand and analyze the effect of workload variables on employees' desire to leave work with work stress as an intervening variable, the study was conducted on employees of PT Fateh Property, Demak Regency. Central Java. The number of employees sampled was all employees with a total of 45 people. The data for this study were obtained through a data collection method using a questionnaire technique that uses a Likert scale. The indicators used in this study are workload indicators, work stress, and employee exit intentions. The hypotheses proposed by this study amounted to 3 hypotheses, where the research hypothesis will be proven by testing quantitative methods using the Sturctural Equation Modeling (SEM) method run through the SmartPLS application. Based on SEM testing, it shows an insignificant positive relationship from workload to turnover intention, a positive and significant relationship from workload to job stress, and a positive and significant relationship from job stress to turnover intention. Then the results obtained from the indirect relationship state that work stress successfully mediates the relationship between workload and turnover intention, so that there is a change in influence from insignificant positive to significant positive. Based on these results, it is known that work stress successfully mediates the effect of workload on turno intention with the perfect mediation category.